Analysis Prudential Principles About The Treath of Phishing Sites For Internet Banking Customers - Andi Siti Nurbaya Sari (Program Studi Perbankan Syariah, IAIN Palopo, 2021)
This thesis is motivated by the existence of an internet site that refers to the act of luring internet banking users to visit fake websites designed by cyber-cybers that resemble the official website in such a way as to trick victims through fake emails (or instant messages) and then secretly take the victim's personal information. . Seeing this requires the precautionary principle regulated by banks to find out customer identities, monitor customer transaction activities including reporting suspicious transactions. The type of research used is the Quantitative Method with 30 samples using a nonprobability sampling technique, namely saturated samples. The instrument used is a questionnaire (questionnaire). Data were processed and analyzed using simple linear regression using SPSS 22 for windows. The results showed that the precautionary principle had a positive effect on the threat of phishing sites by 36.2% with t count (3.982) t table (2.048) with a significant level of 0.000 <0.05. This means that the precautionary principle variable partially has a significant effect on the threat of phishing sites on internet banking at Islamic banks in Palopo city. So it can be concluded that with the precautionary principle of the bank and for customers it can reduce the risk of phishing site threats and more guaranteed security of customer data on internet banking at Islamic banks in Palopo city.